2018
DOI: 10.3892/mmr.2018.8912
|View full text |Cite
|
Sign up to set email alerts
|

Whole‑genome sequencing of a monozygotic twin discordant for systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease, and its genetic causes remain to be fully elucidated. Previous studies have identified several susceptibility genes for SLE, such as deoxyribonuclease 1‑like 3. In the present study, whole‑genome sequencing (30X coverage) was performed on the leukocytes of a monozygotic twin discordant for SLE to assess the potential association of de novo variants and copy number variations (CNVs) with the susceptibility to SLE. After analyzing the genomic data, 8 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Later GWA studies have capitalized on increasing sample sizes, a denser genotyping and reference data set that allow for imputation of non‐typed SNPs, and to date, there are up to 100 SLE risk loci reported 5,28,29 . In addition to these common genetic variants, whole‐exome and whole‐genome sequencing have begun to identify rare genetic SLE risk variants that are not captured in traditional GWA studies 30‐33 . Another field of extensive studies is how epigenetic DNA modifications contribute to SLE 34‐36 …”
Section: The Genetic Background To Slementioning
confidence: 99%
“…Later GWA studies have capitalized on increasing sample sizes, a denser genotyping and reference data set that allow for imputation of non‐typed SNPs, and to date, there are up to 100 SLE risk loci reported 5,28,29 . In addition to these common genetic variants, whole‐exome and whole‐genome sequencing have begun to identify rare genetic SLE risk variants that are not captured in traditional GWA studies 30‐33 . Another field of extensive studies is how epigenetic DNA modifications contribute to SLE 34‐36 …”
Section: The Genetic Background To Slementioning
confidence: 99%
“…Whole exome sequencing (WES) of SLE family trios has identified de novo mutations and potential novel SLE genes (Pullabhatla et al 2018 ). WES has also successfully identified rare variants that are likely pathogenic in SLE (Delgado-Vega et al 2018 ) and WGS of monozygotic twins discordant for SLE has found CNVs that may be associated with difference in SLE phenotype between twins (Chen et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some CNVs loci are commonly implicated in various autoimmune diseases, such as Fcγ receptors in patients with systemic lupus erythematosus or idiopathic thrombocytopenic purpura and β-defensin genes in patients with psoriasis or Crohn’s disease [ 79 , 80 , 81 ]. Another study that compared whole-genome sequence in monozygotic twins revealed that CNVs may be associated with SLE [ 59 ]. Only the genes with discordant copy number losses in SLE patient were significantly enriched in pathways involved in this disease development.…”
Section: Panels Whole-genome and -Exome Sequencing In Diagnosticmentioning
confidence: 99%
“…Sequencing coverage of this study had no sufficient power to identify de novo variants linked with SLE. Therefore, based on WGS only 1 putative discordant exonic variant in GGT1 gene (recorded in the Online Mendelian Inheritance in Man database) between the twins was indicated [ 59 ].…”
Section: Panels Whole-genome and -Exome Sequencing In Diagnosticmentioning
confidence: 99%